صعوبات تعلم مهارة المحادثة باللغة العربية لدى طالبات السنة السادسة الثانوية في المعهد المحمدي للبنات: Difficulties in learning the skill of speaking in Arabic Language among Form Six Students at Maahad Muhammadi Lilbanat - Muhamad, Nur Syafiqah; Zain Aldin, Nurkhamimi (SIBAWAYH Arabic Language and Education, 2021)
الهدف الرئيس من هذه الدراسة هو الكشف عن صعوبات تعلم مهارة المحادثة باللغة العربية لدى طالبات السنة السادسة الثانوية في إحدى المدارس من ولاية كلنتن ألا وهي المعهد المحمدي للبنات بفاسير فكن. ومن المعروف أن، الطالبات يجدن الصعوبات في تعلم هذه اللغة ومن بينها صعوبات في تنمية مهارة المحادثة باللغة العربية على الرغم من أنهن يدرسن هذه اللغة منذ فترة طويلة وهن أيضا الطالبات من المعهد المحمدي للبنات بفاسير فكن وهي إحدى المعاهد المختارة تحت رعاية مؤسسة الإسلامية كلنتن (YIK). وقام الباحثان هذه الدراسة للتعرف على خصائص الفيديو التفاعلي في تنمية مهارة المحادثة باللغة العربية والكشف عن صعوبات في تعلمها. وتسلك هذه الدراسة على خمس الطالبات في السنة السادسة الثانوية وثلاث معلمات اللغة العربية. واستخدم الباحثان المنهج الوصفي من خلال أداة المقابلة وطريقة تحديد العينة بشكل غرضية. ويفترض أن هؤلاء الطالبات يجدن صعوبات في التحدث باللغة العربية واستخدام استراتيجيات التدريس القائم على الفيديو التفاعلي في عملية التعليم والتعلم تمكن أن تحسن مهارة المحادثة لديهنThe main objective of this study is to uncover the difficulties in learning the skill of speaking in the Arabic language among form six students at a school in the state of Kelantan, which is Maahad Muhammadi Perempuan Pasir Pekan. It is known that, students find difficulties in learning this language, including difficulties to develope the skill of speaking in the Arabic language, although they had studied it for a long time and were also students from Maahad Muhammadi Perempuan Pasir Pekan, which is one of the Kelantan Islamic Foundation’s (YIK) preferred school. The two researchers conducted this study to identify the characteristics of the interactive video in developing the skill of speaking in the Arabic language and to know difficulties during learning it. The researcher used the descriptive method through the interview tool and the method for determining the samples were purposefully. The study assumption found that good teaching strategies by using interactive video in teaching and learning process can enhance student’s skills in Arabic.Keywords: Difficulties, form six students, speaking skills in Arabic, interactive video